An adaptive e-learning community of practice for mechanics courses in engineering : final report. - Khawaja, M. Asif (Office for Learning and Teaching, 2013)
Final report from a project that applied artificial intelligence (AI) technology to learning of threshold concepts in undergraduate engineering mechanics in Australian universities. The technology supports interactive virtual laboratory activities (simulations) through which teachers can diagnose common conceptual sticking points in large classes - sticking points that are often missed by 'book and board' teaching and can only picked up by skilled one-to-one coaching. The software allows the teacher to analyse student decisions and then adapt the activity and the feedback given to students on their actions. Pilots in UNSW have established the effectiveness of the tools and method. This project will involve a diverse group of engineering educators from leading Australian universities in extending, spreading and further evaluating the use adaptive tutorials. Furthermore, this project will focus on fostering a community of practice revolving around the use of such technology through a strong focus on staff training and cross-institutional, cross disciplinary, collaboration.